KEBIJAKAN JALUR SUTRA BARU CINA DAN IMPLIKASINYA BAGI AMERIKA SERIKAT - Indriana Kartini (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2015)
The China’s New Silk Road Policy is one of foreign policies from a middle power” country with its rising on economic and military power that in the future could challenge international order dominated by the US. The China’s New Silk Road Policy which consist of two aspects of land (new Silk Road Economic Belt) and maritime (21st Century Maritime Silk Road) is a combination of geopolitics and geoeconomic power to connect Eurasia region with China as the center. This article analyses internal and external factors that drive the China’s government to conduct the policy. Moreover, this article analyses the implementation of the China’s New Silk Road policy and its implications to American hegemony in the world. This article uses concepts such as geopolitic, geoeconomy, foreign policy, and hegemonic stability theory to answer the questions.Keywords: New Silk Road, China, United States of America, foreign policy